Cranial Bone Flap Fixation using a New Device (Cranial LoopTM) - Van Loock, K.; Menovsky, T.; Kamerling, N.; De Ridder, D. (min - Minimally Invasive Neurosurgery, 2011)
Fixation of bone flaps after craniotomy is a routine part of every neurosurgical procedure and there are various options to fixate the bone flap. In this paper, we report on a new cranial bone flap fixation d(Cranial Loop) implanted in 35 consecutive patients.The principle of cranial loop is the same as that of a tie rope. With a simple “pull and tighten” movement, the device is implanted without the need for additional instruments. The cranial loop is made of PEEK [poly(aryl)-ether-ether-ketone] material with the main advantage of being artifact free on postoperative imaging. In 35 consecutive patients operated by a single surgeon, the cranial loops were used for bone flap fixation. All patients had a postoperative CT scanning and a follow-up period of at least 9 months.In all patients, the bone flap could be easily fixed with 3 or more cranial loops without difficulties or material breakage, this within 3 min. The postoperative infection rate was 0%, postoperative hemorrhage (either epi/sub or intraparenchymatous) requiring reoperation was 0%. None of the patients experienced a bone flap dislocation, either clinically or on the postoperative CT-images. 3D CT-scanning revealed all of the flaps being in a good anatomic position.Although this is a preliminary report in a relatively small number of patients, we are of opinion that the cranial loop is a very fast, easy, and safe to use bone flap fixation device with the main advantage of the absence of artifacts on postoperative CT or MR imaging and lack of cosmetic disadvantage.
Keywords: bone flap fixation; craniotomy; PEEK; device